The effects of negative childhood experiences on the severity of mental and substance abuse disorders and recidivism - Gabriel, Christie Lynn (2009)
Overcrowded prisons are a growing problem in the United States. Currently, California prisons are over capacity 85%. Substance abuse increases the likelihood of criminality, for half of state prisoners admitted to being under the influence of drugs or alcohol at the time of their offense(s). A large portion of these individuals, once incarcerated, is also diagnosed with a mental illness. By researching dually diagnosed inmates who were participating in a 90-day in-custody treatment program, this study focuses on how negative family and school experiences become major contributors to adult mental and substance abuse disorders and criminality